Socio-Economic Determinants of Smallholder Tree Plantation in Basona-Werana Woreda in the North Shoa of Amhara Regional State, Ethiopia - Abate, Tensaye; Yohannes, Temesgen (Universitas Sebelas Maret, 2022)
Tree growing by smallholders is an emerging livelihood strategy in Basona-Werana Woreda of the North Shoa Zone of Amhara Regional State. The objective of this study was to identify socio-economic determinants of the smallholder tree growing in the study area. Data were collected from the household survey, key informants and focus group discussions. The binary logistic regression model was employed to identify the socio-economic determinants of smallholder tree growing behavior.Â According to the study, about 55% of tree growers generated their livelihood income from tree planting whereas 72% of non-growers generated income from livestock. Family size of the household and age positively and significantly affected tree planting decisions at P < 0.10 and P < 0.01, respectively. Meanwhile, livestock ownership and distance to the market were negatively and significantly influenced the decision to tree planting at P < 0.01 and P < 0.05, correspondingly. Similarly, total household income positively and significantly (P < 0.01) affected tree planting decisions. This study concluded that the socio-economic circumstances of smallholder farmers must be taken into account in the formulation of initiatives and policies aimed at encouraging smallholders to grow trees in their farming systems to improve livelihood and sustainable agricultural production.